Macrosomia and haemodynamic instability may represent risk factors for subcutaneous fat necrosis in asphyxiated newborns treated with hypothermia. (3rd June 2016) - Courteau, C; Samman, K; Ali, N; Riley, P; Wintermark, P
Abstract: Aim: To identify additional risk factors other than asphyxia and hypothermia in newborns developing subcutaneous fat necrosis (SCFN). Methods: We conducted a prospective cohort study of all term asphyxiated newborns treated with hypothermia from 2008 to 2015. The presence and location of SCFN were recorded at the time of discharge or at follow‐up visits. To identify the risk factors for developing SCFN, we compared the perinatal characteristics of those newborns who developed SCFN with those who did not. Results: The newborns developing SCFN had significantly higher birthweights compared with those newborns who did not develop SCFN. Among the newborns with a birthweight equal or superior to the 90th percentile, those who developed SCFN had a significantly higher use of inotropic support and higher maximum troponin levels during their initial hospitalisation. Conclusion: A higher birthweight represented an independent risk factor for developing SCFN in asphyxiated newborns treated with hypothermia. When macrosomia is present, other risk factors related to haemodynamic instability during the initial hospitalisation may also increase the risk of developing SCFN.